Analisis kinerja keuangan pada sektor consumer cyclicals yang terdaftar di BEI periode 2020 - 2023 - Tjhin, Erwin; Gamaliel, Hendrik; Pinatik, Sherly (Riset Akuntansi dan Manajemen Pragmatis, 2024)
Financial performance analysis is really needed in a company in order to see the extent of the company's financial performance over a certain period of time. This financial performance analysis can help the company in making decisions in the future. Analysis of financial performance in a company can be seen using financial ratio analysis. This research aims to determine differences in the financial performance of the Consumer Cyclicals sector, especially the media and entertainment sub-sector for the 2020-2023 period. This type of research is a descriptive statistical approach. The analysis method used is trend analysis. The research results show that there is an increase or decrease in the media and entertainment sub-sector listed on the Indonesian stock exchange for the 2020-2023 period using the debt to asset ratio, net profit margin, current ratio and total asset turnover.